Detection of organochlorine compound in puyu, sepat and haruan fish caught from irrigation canals in paddy fields in Selangor and Perak, Malaysia - Abdul Rahman, Nur Azhani; Omar, Mohamed Ariff (2012)
A case study was conducted to investigate the concentration of organochlorine pesticide residues in fish samples collected from irrigation canals in paddy fields in Tanjong Karang and Sekinchan, Selangor and Seberang Perak, Perak, Malaysia. The samples comprised of three fish species, namely puyu (Anabas testudineus), haruan (Channa striatus) and sepat (Tricogaster pectoralis). Samples were chopped and homogenized and later digested and extracted using QuEChERS method and characterised for organochlorine compounds using gas chromatography. Seven organochlorine compounds, namely aldrin, dieldrin, endrin, endosulfan, o,p-DDT, o,p-DDD and p,p-DDT were identified and quantified. The water samples taken from the irrigation canals were analysed only for endosulfan at 0.04 mg/kg, which exceeded the maximum residue level for endosulfan pesticide residue for water sewage by Environment Protection Administration of the Republic of China on Taiwan (2000) at 0.03 mg/kg. However, the concentrations of endosulfan in all fish samples were below the Codex Alimentary Maximum Residue Limit of 0.2 mg/kg for meat.